2021
DOI: 10.1155/2021/1620891
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Effect of Probiotics in Gastric Cancer Patients with Complications of Coronary Heart Disease and Heart Failure

Abstract: Objective. To investigate the characteristics of intestinal flora in patients with gastric cancer complicated by coronary heart disease and heart failure and the guiding value of probiotics intervention for clinical treatment. Methods. (1) One hundred and sixty-eight gastric cancer patients with complications of coronary heart disease and heart failure from August 2017 to December 2020 were selected as the observation group. A total of 125 patients with coronary heart disease treated at the same time were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Gastric cancer is a fatal tumor with high incidence, and the age of onset tends to be younger with the change of daily dietary structure [ 14 ]. In clinical application at the present stage, ultrasound gastroscopy and other related imaging examinations are generally used for early screening of patients [ 15 ], and surgical treatment, targeted therapy and chemotherapy are used for ameliorative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is a fatal tumor with high incidence, and the age of onset tends to be younger with the change of daily dietary structure [ 14 ]. In clinical application at the present stage, ultrasound gastroscopy and other related imaging examinations are generally used for early screening of patients [ 15 ], and surgical treatment, targeted therapy and chemotherapy are used for ameliorative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to patients with HF alone, a previous clinical trial focused on gastric cancer patients with coronary heart disease and HF complications because apparent intestinal disorders are consistently observed in such populations and they stimulate HF progression 170 . In patients with gastric cancer with coronary heart disease and HF, probiotic capsules containing B. longum enhanced the intestinal barrier and corrected intestinal microbial imbalance as well as HF, thereby promoting patient rehabilitation 170 .…”
Section: Current Applications In Cardiovascular Diseasementioning
confidence: 99%
“…Recently, a randomized clinical trial, in which 90 participants had been followed up, revealed that the probiotic yogurt was able to reduce the serum oxLDL and suppress the oxidative reaction in HF patients ( Pourrajab et al, 2020 ). Further, another study found that the intestinal barrier was a potential therapeutic target for HF, and a combined probiotic intervention is capable of repairing gut mucosa ( Yu et al, 2021 ). Besides, in an animal model, the cardioprotective effect of probiotics was also identified.…”
Section: Interventions Targeted At Microbial Metabolitesmentioning
confidence: 99%